A pharmacoeconomic analysis of the use of single MMC instillation in low risk NMIBC in Italy - Colombo, Renzo; Pellucchi, Federico; Rocchini, Lorenzo; Maccagnano, Carmen; Katz, Pablo; Pegoraro, Valeria (Farmeconomia. Health economics and therapeutic pathways, 2013)
BACKGROUND: Bladder cancer accounts for 5-10% of all cancers in Europe and up to 85% patients presents a noninvasive tumor, whose treatment of choice is the transurethral bladder resection (TURB) paired with adjuvant intravesical chemotherapy or immunotherapy. Despite several clinical trials showed that this treatment is safe and decreases recurrences by 17% to 44% this practice is limited for many reasons. The study objective is to analyze the economical advantages of the single immediate post operative Mitomycin C instillation in Non Muscle-invasive Bladder Cancer (NMIBC) low-risk patients. METHODS: A cost-benefit analysis was performed evaluating the economical gain that would raised from a scenario with a single immediate post operative mitomycin C instillation in each low-risk NMIBC patient who underwent to TURB. Net present value and cost-benefit ratio were calculated and sensitivity analyses were performed. Base case analysis was performed considering tumor recurrence rate reduction of 11.7% and a TURB costs of 2,167.0 €, while sensitivity analyses were performed using a recurrence rate reduction of 19.2% and 15.0% and a TURB cost of 2,472.93 €. The discount rate was 2%. RESULTS: The single immediate post operative instillation of mitomycin C resulted to be cost-beneficial with a cost-benefit ratio that goes from 0.48 to 0.79 when compared to TURB alone raising a Net Present Value that goes from 660,284.39 € to 2,650,530.79 €. CONCLUSION: This study demonstrates that even assuming conservative parameters for recurrence rates reduction, a single immediate post operative mitomycin C instillation in low risk NMIBC patients would lower not only the recurrence rate but also the caring cost for bladder cancer.